2018
DOI: 10.7196/sajch.2018.v12i4.1449
|View full text |Cite
|
Sign up to set email alerts
|

Impact of atopic dermatitis on the quality of life of Nigerian children: A hospital-based cross-sectional study

Abstract: Background. Atopic dermatitis (AD) is the most common inflammatory skin disease in childhood. A skin disorder with a relapsing course, AD exerts a significant disease burden on affected children. However, there is a dearth of knowledge about the impact of AD on the quality of life (QOL) of affected children in Nigeria. Objectives. To examine the impact of AD on QOL in children of various age groups, and to identify the relationship between patient variables (age, gender, socioeconomic status), disease severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
(62 reference statements)
2
6
0
Order By: Relevance
“…This is similar to the conclusions drawn from other studies, however Durovic et al showed that children with AD between the age of 5-9 years had most impaired QoL. 5,2,22 The impairment of QoL was not found to be gender specific in the current study, although some authors have reported gender differences in the impact of AD in QoL of children. 7,23,24 Although the QoL scores were found to be higher in the upper lower class compared to all other socio-economic classes and among children with early onset disease.…”
Section: Correlation With Patient Variablessupporting
confidence: 92%
See 3 more Smart Citations
“…This is similar to the conclusions drawn from other studies, however Durovic et al showed that children with AD between the age of 5-9 years had most impaired QoL. 5,2,22 The impairment of QoL was not found to be gender specific in the current study, although some authors have reported gender differences in the impact of AD in QoL of children. 7,23,24 Although the QoL scores were found to be higher in the upper lower class compared to all other socio-economic classes and among children with early onset disease.…”
Section: Correlation With Patient Variablessupporting
confidence: 92%
“…6,16,18,19 The occurrence of pruritus as a major contributor to the magnitude of the QoL scores, also displayed a similar trend in comparison to the existing literature. 2,5,20 In addition to this, the sleep latency and quality of sleep also contributed heavily to the QoL scores, which might be secondary to the occurrence of night pruritus. Numerous authors have made similar observations about the impact of sleep disturbances.…”
Section: Correlation With Patient Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…The diagnosis of atopic dermatitis is made using the Hanifin and Rajka criteria. This requires that the individual presents with a pruritic rash and three or more of the following features: history of rash in the skin creases (fold of the elbow, behind the knees, front of the ankles and around the neck), a personal or family history of asthma and hay fever, history of generalized dry skin (xerosis), onset before the age of 2 years and visible flexural dermatitis [22]. In 2004 Nnoruka, noted that the symptoms these children present with varies according to ethnicity [23].…”
Section: Introductionmentioning
confidence: 99%